Putin : Russia's choice - Sakwa, Richard (New York : Routledge, 2004)
"Drawing on both Russian and English-language sources, and providing comprehensive coverage of Putin's speeches, interviews and policy documents, this is the definitive study of the Russian leader."--BOOK JACKET.
1. The unlikely path to power -- 2. The ideas behind the choice -- 3. The Putin way -- 4. State and society -- 5. Restructuring political space -- 6. Putin and the regions -- 7. Reforging the nation -- 8. Russian capitalism -- 9. Putin and the world -- 10. Conclusion -- App. Russia at the turn of the millennium.
Includes index.
Bibliography, p. [293]-295.
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Russia (Federation) -- Politics and government -- 1991-